2017
DOI: 10.1002/cne.24335
|View full text |Cite
|
Sign up to set email alerts
|

Neural stem/progenitor cells are activated during tail regeneration in the leopard gecko (Eublepharis macularius)

Abstract: As for many lizards, the leopard gecko (Eublepharis macularius) can self-detach its tail to avoid predation and then regenerate a replacement. The replacement tail includes a regenerated spinal cord with a simple morphology: an ependymal layer surrounded by nerve tracts. We hypothesized that cells within the ependymal layer of the original spinal cord include populations of neural stem/progenitor cells (NSPCs) that contribute to the regenerated spinal cord. Prior to tail loss, we performed a bromodeoxyuridine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 132 publications
(225 reference statements)
3
40
0
Order By: Relevance
“…Previous ultrastructural and autoradiographic studies (Alibardi, 1990‐91, ) and more recent immunohistochemical studies (Gilbert & Vickaryous, ; Zhou et al., ) have indicated that progenitor/stem cells give rise to most glial and few neural cells during tail regeneration. While HMGb1 appears to stimulate regeneration and contrast inflammation after wounding (Dong et al., ), HMGa2 detected in ependymal cells instead likely indicates the presence of progenitor‐stem cells in these cells (Gilbert & Vickaryous, ; Zhou et al., ).…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Previous ultrastructural and autoradiographic studies (Alibardi, 1990‐91, ) and more recent immunohistochemical studies (Gilbert & Vickaryous, ; Zhou et al., ) have indicated that progenitor/stem cells give rise to most glial and few neural cells during tail regeneration. While HMGb1 appears to stimulate regeneration and contrast inflammation after wounding (Dong et al., ), HMGa2 detected in ependymal cells instead likely indicates the presence of progenitor‐stem cells in these cells (Gilbert & Vickaryous, ; Zhou et al., ).…”
Section: Discussionmentioning
confidence: 98%
“…The immunofluorescent study has shown that the main localization of a HMGa2‐like protein occurs in tissues that drive tail regeneration, namely the apical wound epithelium and the regenerating spinal cord, mainly composed by an ependymal epithelium (Alibardi & Sala, ; Alibardi, Sala, & Miolo, ; Alibardi, 1990‐91, ; Alibardi, ; Cox, ; Gilbert & Vickaryous, ; Simpson, ; Zhou et al., ). These tissues show an active proliferation that is maintained in the apical regions of the regenerating tail while in proximal regions of the blastema, 1–2 mm from its tip, proliferation becomes less frequent and cells begin to differentiate into numerous tissue types.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations